2008
DOI: 10.1080/08870440701615260
|View full text |Cite
|
Sign up to set email alerts
|

Predicting breastfeeding in women living in areas of economic hardship: Explanatory role of the theory of planned behaviour

Abstract: This study employed the theory of planned behaviour (TPB) and additional variables (descriptive norm, moral norm, self-identity) to investigate the factors underlying breastfeeding intention and subsequent breastfeeding at four time points (during hospital stay, at hospital discharge, 10 days postpartum and 6 weeks postpartum) in a sample of women selected from defined areas of economic hardship (N = 248). A model containing the TPB, additional variables and demographic factors provided a good prediction of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
5
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 55 publications
6
88
5
2
Order By: Relevance
“…However, even in this sample there was a considerable reduction in the rate of breastfeeding in the first 6 weeks (from 99% to 79%), and identifying the important factors associated with those who continue or stop breastfeeding by this stage is important. Furthermore, where the variables and analyses were similar to previous studies, the findings were also similar – even when compared to a deprived sample (McMillan et al ., 2008, 2009). This suggests that many of the factors associated with infant feeding, and in particular the relative importance of past experience and self‐efficacy, may be similar across socio‐economic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in this sample there was a considerable reduction in the rate of breastfeeding in the first 6 weeks (from 99% to 79%), and identifying the important factors associated with those who continue or stop breastfeeding by this stage is important. Furthermore, where the variables and analyses were similar to previous studies, the findings were also similar – even when compared to a deprived sample (McMillan et al ., 2008, 2009). This suggests that many of the factors associated with infant feeding, and in particular the relative importance of past experience and self‐efficacy, may be similar across socio‐economic groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, one which measured intentions before giving birth found that they were a strong predictor of behaviour, with r  = .67 for breastfeeding initiation and r  = .42 for breastfeeding at 6 weeks (McMillan et al ., 2008). Other prospective studies have shown direct associations (not mediated by intentions) between breastfeeding behaviour and attitudes, subjective norms, and PBC/self‐efficacy (Duckett et al ., 1998; Lawton et al ., 2012; Manstead, Plevin, & Smart, 1984; Manstead, Proffitt, & Smart, 1983; McMillan et al ., 2008). Therefore, there is evidence that the components of the TPB are relevant to understanding infant feeding intentions and behaviour, although they may not be best operationalized in the TPB model.…”
Section: Introductionmentioning
confidence: 99%
“…Distributions and ranges of scores, along with means, standard deviations, skewness, and kurtosis (where appropriate) were inspected. The potentially confounding socio-demographic variables included gender, race/ethnicity, parental income, and parental education (Nommsen-Rivers et al, 2010;Khoury et al, 2005;McMillan et al, 2008). These were entered in to the regression equations to examine simultaneously the relationships of these socio-demographic variables and the factors of feeding intent to the outcome measures.…”
Section: Data Analysesmentioning
confidence: 99%
“…There is a gap, known worldwide, in the intention-behavior relationship (10) . The fragile intentionbehavior relationship is mostly due to people expressing good intentions, but failing to implement them (11) . So, implementation intentions can enhance the initiation of action, since they are secondary to intentions and act through the specification of when, where, and how the behavior will be performed (12) .…”
Section: Introductionmentioning
confidence: 99%